On the “Viking” presence in Nunavik: Much ado about nothing! - Gendron, Daniel (Études/Inuit/Studies, 2015)
Back in the 1950s, Dorset longhouses were unknown to archaeologists working in the Arctic. The discovery of one near Kangirsuk (Nunavik) in the early 1960s was an important addition to the corpus of data on the Dorset culture, but it was never presented as such by Thomas Lee. Somehow, this discovery was twisted into something else, and although Dorset longhouses are today being recognized in different parts of the Arctic world, the Imaha site at Pamiok Island carries false ghosts from the past. Following unsubstantiated conclusions from archaeological work done there in the mid-1960s, the Kangirsummiut still believe the site is of Viking origin, and this myth is being carried on outside Nunavik by visitors who are not informed better. This essay aims to end this charade once and for all and restore the true nature of the Imaha site.